Carotid Endarterectomy: Comparison of Complications Between Transverse and Longitudinal Incision. Issue 2 (21st March 2014) - Mendes, George A. C.; Zabramski, Joseph M.; Elhadi, Ali M.; Kalani, M. Yashar S.; Preul, Mark C.; Nakaji, Peter; Spetzler, Robert F.
Abstract: BACKGROUND: Cranial nerve injury (CNI) is the most common neurological complication associated with carotid endarterectomy (CEA). Some authors postulate that the transverse skin incision leads to increased risk of CNI. OBJECTIVE: We compared the incidence of CNI associated with the transverse and longitudinal skin incisions in a high-volume cerebrovascular center. METHODS: We reviewed the charts of 226 consecutive patients who underwent CEAs between January 2007 and August 2009. Pre- and postoperative standardized neurological evaluations were performed by faculty neurologists and neurosurgeons. RESULTS: One hundred sixty nine of 226 (75%) CEAs were performed with the use of a transverse incision. The longitudinal incision was generally reserved for patients with a high-riding carotid bifurcation. Mean patient age was 69 years (range, 45–91 years); 62% were men; 59% of patients were symptomatic and had high-grade stenosis (70%-99%). CNI occurred in 8 cases (3.5%): 5 (3%) in transverse and 3 (5.3%) with longitudinal incisions ( P = .42). There were 2 marginal mandibular nerve injuries, 1 (0.6%) transverse and 1 longitudinal; 5 recurrent laryngeal nerve injuries, 4 transverse and 1 longitudinal; and 1 case of hypoglossal nerve injury associated with longitudinal incision. One hematoma was associated with CNI. All injuries were transient. Fourteen wound hematomas required surgical evacuation. CONCLUSION: The transverse skin incision for CEAs is not associated with an increased risk of CNI ( P =.42). In this study, the incidence of CNI associated with the transverse incision was 3% (n = 5) vs 5% (n = 3) for longitudinal incisions. All CNIs were temporary.